1999
DOI: 10.1152/ajplung.1999.277.1.l167
|View full text |Cite
|
Sign up to set email alerts
|

Stretch induces cytokine release by alveolar epithelial cells in vitro

Abstract: Mechanical ventilation can injure the lung, causing edema and alveolar inflammation. Interleukin-8 (IL-8) plays an important role in this inflammatory response. We postulated that cyclic cell stretch upregulates the production and release of IL-8 by human alveolar epithelium in the absence of structural cell damage or paracrine stimulation. To test this hypothesis, alveolar epithelial cells (A549 cells) were cultured on a deformable silicoelastic membrane. When stretched by 30% for up to 48 h, the cells releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
282
0
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(309 citation statements)
references
References 35 publications
16
282
0
9
Order By: Relevance
“…By using in situ hybridization, FODA et al [32] showed activation of the extracellular matrix metalloprotein inducer (EMMPRIN), gelatinase A and gelatinase B, in alveolar macrophages, alveolar epithelial cells and endothelial cells from rats ventilated with 20 mL?kg -1 and no PEEP for 4 h [32]. In the present study, [33] and IL-8 from stretched alveolar epithelial cells [34]. Indirect evidence of the type II cells9 responsiveness to stretch was already provided almost 20 yrs ago, when it was shown that even one single deep breath is sufficient to release pulmonary surfactant [35].…”
Section: Discussionmentioning
confidence: 48%
“…By using in situ hybridization, FODA et al [32] showed activation of the extracellular matrix metalloprotein inducer (EMMPRIN), gelatinase A and gelatinase B, in alveolar macrophages, alveolar epithelial cells and endothelial cells from rats ventilated with 20 mL?kg -1 and no PEEP for 4 h [32]. In the present study, [33] and IL-8 from stretched alveolar epithelial cells [34]. Indirect evidence of the type II cells9 responsiveness to stretch was already provided almost 20 yrs ago, when it was shown that even one single deep breath is sufficient to release pulmonary surfactant [35].…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, inhaled CO also reduced BALF macrophage numbers at 2 hours. TNF-␣ is a well known and well investigated cytokine that has a proinflammatory effect in in vivo and in vitro models (10,30), and IL-10 has antiinflammatory activity in LPS-induced inflammation (31). It is interesting to note that CO did not affect the BALF protein levels, suggesting that CO exerts negligible effects on pulmonary permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil recruitment to the lungs might be a critical step in the pathogenesis of ventilator-induced lung injury (18,33). The likely cellular sources of IL-8 in the lung are the respiratory epithelium and alveolar macrophages (16,42).…”
mentioning
confidence: 99%